2012
DOI: 10.1007/s11060-012-0886-4
|View full text |Cite
|
Sign up to set email alerts
|

Atypical and anaplastic meningiomas treated with bevacizumab

Abstract: Atypical and anaplastic (WHO Grades II and III) meningiomas are aggressive tumors, and patients often progress despite surgery and radiation. There is no known effective chemotherapeutic option for these patients. Meningiomas have a high expression of vascular endothelial growth factor receptor (VEGFR). We sought to retrospectively study the activity of bevacizumab, which is an anti-angiogenic agent targeting the VEGF pathway in these tumors. This is a retrospective review of WHO Grade II and III meningiomas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 7 publications
1
90
0
2
Order By: Relevance
“…39,65 This relative success must be tempered, however, by the high rate of side effects and the low median overall survival (OS) with chemotherapy for these surgery-and radiation-refractory Grade II and III meningiomas, at approximately 24 months. 39,55,56,65 Chemotherapy for AMs shows promise but should only be considered for select refractory tumors as salvage therapy.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…39,65 This relative success must be tempered, however, by the high rate of side effects and the low median overall survival (OS) with chemotherapy for these surgery-and radiation-refractory Grade II and III meningiomas, at approximately 24 months. 39,55,56,65 Chemotherapy for AMs shows promise but should only be considered for select refractory tumors as salvage therapy.…”
Section: Chemotherapymentioning
confidence: 99%
“…Conversely, select trials have suggested that angiogenesis inhibitors may play a role in salvage therapy for recurrent or refractory MMs (EBM Level 2, Grade 2B recommendation). 39,55,56,65 Clearly, additional studies are needed for these formidable meningiomas.…”
Section: Chemotherapymentioning
confidence: 99%
“…16 Several studies have also indicated that VEGF and VEGFR antagonists have roles in the treatments of other brain tumors, including vestibular schwannomas, meningiomas, and low-grade astrocytomas. 5,[7][8][9]11,12,17,18 Despite being nonmalignant brain tumors, vestibular schwannomas and meningiomas carry significant morbidity and risk of mortality for certain patients. Many but not all of these tumors can be treated with surgery or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab oder Sunitinib [30,31]. Therapieversuche mit dem Somatostatin-RezeptorAgonisten Octreotid waren weitgehend erfolglos [32].…”
Section: In Diesem Beitrag Werden Therapiestandards Und Neue Entwicklunclassified